Meningkatkan Kemampuan Pemecahan Masalah melalui Problem-Based Learning pada Pembelajaran Matematika Kelas IV SD - Kurniawati, Dewi; Tiurlina, Tiurlina; Alfarisa, Fitri (Universitas Pendidikan Indonesia Kampus Serang, 2021)
Students' ability in program solving in math subjects is still low, this is based on results of the 1st semester of 2021 math test at SDN Cilegon 04. Existing research has a goal that is (1) Knowing the problem-solving skills of grade IV students through problem-based learning (PBL) on math learning in the experimental class (2) Knowing the problem-solving skills of grade IV students through conventional learning in a control class mathematics (3) Knowing the existence or absence of improved problem-solving skills of grade IV student through problem-based learning in mathematics learning in the experimental class. In this case, existing research can use the experimental method, true experimental type pre-test, and post-test, existing sampling methods can be taken with a random sampling cluster method so that existing students number 54 students and consist of 27 students as experiments and 27 students’ controls. The result of this study can be seen that (1) there is a difference in grades with a difference of 24,54 between the pre-test and post-test in terms of students' learning habits by PBL in experimental class math learning, (2) learning results using conventional methods in math subjects obtained pre-test and post-test differences with an average of 10,18 in the control class, (3) through the PBL learning methods of mathematics subjects in the experimental class there is an increase in solving a problem with the comparison of the result between the experimental class and the control class the difference between two is 6,943 and the Sig (2 tailed) value obtained is 0,0000,05. These results show that there is a significant impact of PBL learning on students' problem-solving abilities and these results can be used as a basis for good teacher learning practices in subsequent classes.